Confinement of Pregnant Women for Protection of the Unborn - Chris O. Abakare (Universitas Negeri Makassar, 2020)
The conflict between the rights of women and unborn take an ugly turn when one speaks of confinement of women for protection of their foetuses. The very thought seems perverse because we delve into the negative aspect of the rights discourse - rights are in modern times used as weapon to correct moral depravity. The relationship between the mother and her foetus, particularly the aspect of maternal care towards the unborn is more a matter of course than rights’. Thus, in case of pregnant women-foetal relationship, what essentially was a part of maternal responsibility and innate to motherhood gets reduced to rights and becomes a matter of legal duty rather than a moral responsibility. From the moral-philosophical perspective, it may be viewed as a debasement of the relationship from both sides - the mother refuses to alter her lifestyle of addiction for the sake of the unborn upon which the latter is up in arms against the former with the charge of abuse. This work maintains that the rights discourse is ill equipped to understand the problem, as law cannot be perceived as the panacea of all ills.